Protective Effect Of Phenorbarbitone And Griseofulvin Againt Signal Grass (Brachiaria Decumbens)Toxiciti In Sheep - Ab. Hamid, Hasiah (2001)
The protective effect of phenobarbitone and griseofulvin against signal grass (B. decumbens) toxicity were studied in fifty-three Wiltshire x Malin (Indigenous Malaysian) male sheep. Twenty-six animals were used in phenobarbitone experiment and twenty-seven animals were used in griseofulvin experiment. Grazing on signal grass significantly decreased the concentration of cytochrome P-4S0 and the activity of drug metabolizing enzyme, viz. aminopyrine-N-demethylase, aniline-4- hydroxylase, UDP-glucuronyltransferase and glutathione-S-transferase in liver and kidney of sheep. The concentration of cytochrome P-4S0 was determined in microsomal fraction according to the method of Omura and Sato (1964a) as described by Mazel (1971). The activities of aminopyrine-N-demethylase and aniline-4- hydroxylase were determined using Mazel, 1971 method by estimating the